Difference between revisions of "1976 AHSME Problems/Problem 1"

(Solution)
(Solution)
Line 7: Line 7:
 
== Solution ==
 
== Solution ==
  
The reciprocal of <math>(1-x)</math> is <math>\frac{1}{1-x}</math>, so our equation is <cmath>1-\frac{1}{1-x}=\frac{1}{1-x},</cmath> which is equivalent to <math>\frac{1}{1-x}=\frac{1}{2}</math>. So, <math>1-x=2</math> and <math>x=-2\Rightarrow \textbf{(A)}</math>.
+
The reciprocal of <math>(1-x)</math> is <math>\frac{1}{1-x}</math>, so our equation is <cmath>1-\frac{1}{1-x}=\frac{1}{1-x},</cmath> which is equivalent to <math>\frac{1}{1-x}=\frac{1}{2}</math>. So, <math>1-x=2</math> and <math>x=-2\Rightarrow \textbf{(A)}</math>.~MathJams

Revision as of 21:48, 11 July 2020

Problem 1

If one minus the reciprocal of $(1-x)$ equals the reciprocal of $(1-x)$, then $x$ equals

$\textbf{(A) }-2\qquad \textbf{(B) }-1\qquad \textbf{(C) }1/2\qquad \textbf{(D) }2\qquad  \textbf{(E) }3$

Solution

The reciprocal of $(1-x)$ is $\frac{1}{1-x}$, so our equation is \[1-\frac{1}{1-x}=\frac{1}{1-x},\] which is equivalent to $\frac{1}{1-x}=\frac{1}{2}$. So, $1-x=2$ and $x=-2\Rightarrow \textbf{(A)}$.~MathJams

Invalid username
Login to AoPS